Cover Picture: Di‐tert‐butyldiphosphatetrahedrane: Catalytic Synthesis of the Elusive Phosphaalkyne Dimer (Angew. Chem. Int. Ed. 47/2019). Issue 47 (30th October 2019) - Hierlmeier, Gabriele; Coburger, Peter; Bodensteiner, Michael; Wolf, Robert
Abstract : Di‐tert‐butyldiphosphatetrahedrane, a tetrahedral molecule comprised of phosphorus and carbon atoms, is described by R. Wolf and co‐workers in their Communication on page 16918. This metastable compound was previously predicted by theoretical calculations as a key intermediate in the oligomerization of phosphaalkynes. The synthesis of this elusive phosphaalkyne dimer on a preparative scale through a nickel‐catalyzed process closes a significant gap in the chemistry of phosphaalkynes.